Uric Acid Dynamics in Young Women: Associations with Radiation Exposure, Blood Groups, and Biochemical Markers - Ahmed, Ahmed H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
A growing body of evidence implicates uric acid to play central roles in various disease complications. However, the delineation between causative and coincidental roles remains poorly elucidated. This study aimed to evaluating uric acid in young women considering variables such as disease types, body mass index, blood groups, radiation exposure, and to assess the relationship between uric acid levels and certain subclinical biomarkers. A cohort of 178 young women, between 18 and 39 years, (comprising 100 cases and 78 healthy controls) was included in this investigation. Diagnosed subjects with common diseases, renal, cardiovascular, blood, joints, diabetes, gastrointestinal diseases, were selected according to stringent criteria. Subjects were categorized based on disease types, blood groups, and exposure history to ionizing radiation including mammography and body or leg X-ray. Serum levels of uric acid and biochemical tests were analyzed by unpaired comparison tests and correlation coefficient tests. Subjects with hematological disorders exhibited lower uric acid concentrations when compared to healthy women. Uric acid concentrations in individuals with repeated exposure to X-ray radiation showed a high significant difference (p<0.01) compared to unexposed individuals. In Spearman correlation analyses, positive correlations (p < 0.001) are identified between uric acid and iron, calcium, prolactin, and body mass index. In healthy young women, uric acid levels fluctuated both within and beyond physiological ranges, independent of disease status, weight indexes, and blood types. Assessment of uric acid in young women, based on a history of radiation exposure, subclinical blood parameters might guide for better medical decision and treatment.